Studi Pendekatan Biofilik pada Rumah Sakit Tipe C di Area Relokasi Erupsi Semeru Kabupaten Lumajang (Selasar, 2023)
Lumajang city has six hospitals that can be used by the people, but has a very far distance from residential areas around Mount Semeru, especially in the relocation area for survivors of the Mount Semeru eruption. The design of a type C hospital in the relocation area of Mount Semeru eruption survivors is a manifestation of disaster risk management through programs and policies to minimize the impact of disasters. The method of discussion is a descriptive qualitative with the literature studies as the main sources. The design process used leads to a repeated continuously process. Design using biophilic architecture is a design that provides an opportunity for people to live in a healthy environment, a place that can reduce stress by integrating natural elements into the design. This is according to the patient’s condition who requires elements of environment that can accelerate recovery. Biophilic architectural approaches that can support the patient's healing process, such as providing a garden as the main orientation, green walls, skylight, and static rooms with balconies come with colorful plants such as bougenville, rose, and hibiscus that are pleasing to the eye.